Downregulation of Microglial Activation by Achillolide A - Elmann, Anat; Telerman, Alona; Mordechay, Sharon; Erlank, Hilla; Rindner, Miriam; Kashman, Yoel; Ofir, Rivka (Planta Medica, 2015)
Chronic inflammation has been implicated in the pathogenesis of various neurodegenerative diseases. During the neuroinflammatory process, microglial cells release neurotoxic and proinflammatory mediators. In the present study, using activity-guided fractionation, we have purified an anti-inflammatory compound determined by spectroscopic methods to be a sesquiterpene lactone named achillolide A from Achillea fragrantissima (Forsk.) Sch. Bip. In primary cultures of lipopolysaccharide-activated microglial cells, achillolide A inhibited the lipopolysaccharide-induced levels of proinflammatory and toxic mediators including glutamate, nitric oxide, matrix metalloproteinase-9, cyclooxygenase-2, induced nitric oxide synthase, interleukin-1β, and tumor necrosis factor-α. Achillolide A also exhibited an antioxidant capacity, as was shown in a cell free system as well as by its ability to reduce intracellular reactive oxygen species levels in microglial cells. Thus, achillolide A might have therapeutic potential for treatment of neurodegenerative diseases and deserves further studies.
Keywords: Achillea fragrantissima; Asteraceae; achillolide A; microglial cells; inflammation; neurodegenerative diseases